Timing of Side-Dress Applications of Nitrogen for Corn in Conventional and No-Till Systems - D. W. Sweeney; D. Ruiz Diaz (Kansas Agricultural Experiment Station Research Reports, 2020)
Corn yield and yield components were affected by tillage and nitrogen (N) side-dress application options in 2019. Average corn yields were 15% greater with conventional tillage than with no-till. Yields were improved by either splitting N rate between pre-plant and side-dress at the V10 growth stage or adding additional side-dress N as compared with applying 150 lb/a pre-plant.
Keywords: nitrogen; timing; side-dress; corn; tillage